Pengembangan Media Balik Kotak Angka Brawas untuk Pembelajaran Pengenalan Angka Tunanetra - Riska Aisyah Lubis; Fatmawati Fatmawati (Universitas Negeri Padang, 2022)
Starting from blind children who experience problems in recognizing numbers, and that is due to the absence of media that supports the learning process, causing something that should be known and understood, not at all known by children in learning, namely for learning basic mathematics such as recognizing numbers. This study aims to find out how to develop the media for the visually impaired square number box and to determine the feasibility of the square block media that has been developed by researchers in development research. This study uses a research and development approach to Research and Development (R&D). The result of this research is that the braille number box media is a suitable medium for blind children to use.